2021
DOI: 10.1021/acs.jpca.0c09168
|View full text |Cite
|
Sign up to set email alerts
|

Nitromethane Decomposition via Automated Reaction Discovery and an Ab Initio Corrected Kinetic Model

Abstract: We explore the systematic construction of kinetic models from in silico reaction data for the decomposition of nitromethane. Our models are constructed in a computationally affordable manner by using reactions discovered through accelerated molecular dynamics simulations using the ReaxFF reactive force field. The reaction paths are then optimized to determine reaction rate parameters. We introduce a reaction barrier correction scheme that combines accurate thermochemical data from density functional theory wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…Recent results that first enumerate a reaction network and then calculate rate parameters have been able to capture important features but not completely match atomistic simulations. 200 Aside from the assumptions inherent to transition state theory, it is also not certain that reaction barriers calculated by looking at isolated reactions still hold when looking at the potential energy surface of the whole system. For high-temperature, high-pressure systems, it has also been shown that, in addition to reactions involving stable states, transient species may play a critical role in reaction dynamics.…”
Section: The Many-body Roadmapmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results that first enumerate a reaction network and then calculate rate parameters have been able to capture important features but not completely match atomistic simulations. 200 Aside from the assumptions inherent to transition state theory, it is also not certain that reaction barriers calculated by looking at isolated reactions still hold when looking at the potential energy surface of the whole system. For high-temperature, high-pressure systems, it has also been shown that, in addition to reactions involving stable states, transient species may play a critical role in reaction dynamics.…”
Section: The Many-body Roadmapmentioning
confidence: 99%
“…Coarse-Graining to Macroscales. In recent years, automatic learning of large chemical reaction networks from atomistic simulation data has been explored, 195,200,201 enabling these reaction networks to then be simulated using kinetic models, either through stochastic simulation or rate equations. This enables orders of magnitude faster propagation in both space and time.…”
Section: Coarse-graining Timementioning
confidence: 99%
“…10, we can observe that at 2,800 K the system needs around 1-10 ns to come to equilibrium with a system starting with CH 4 or with C 4 H 10 , which is the same order of magnitude as the experiments run by Kraus et al Therefore, our model points out that Kraus et al's experiments are on timescales close to the time needed for equilibrium to be reached. It is important to notice that our model is fit on the ReaxFF potential, but ReaxFF has been shown to sometimes fail to reproduce ab initio energies [8] and some common reactions are not observed in ReaxFF simulations [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been used to investigate the evolution of complex systems in conditions where atomistic simulations cannot be performed in reasonable time. Ford et al [8] developed a method based on a nanoreactor [9] that pushes molecules together so they react more often. With this method, reactions are sampled faster; nonetheless, no information about the rate coefficients can be extracted because pressure and temperature are not well-defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation